Isolated leucine and branched-chain amino acid supplementation for enhancing muscular strength and hypertrophy: A narrative review - Plotkin, D. L.; Delcastillo, K.; Van Every, D. W.; Tipton, K. D.; Aragon, A. A.; Schoenfeld, B. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
Branched-chain amino acids (BCAA) are one of the most popular sports supplements, marketed under the premise that they enhance muscular adaptations. Despite their prevalent consumption among athletes and the general public, the efficacy of BCAA has been an ongoing source of controversy in the sports nutrition field. Early support for BCAA supplementation was derived from extrapolation of mechanistic data on their role in muscle protein metabolism. Of the three BCAA, leucine has received the most attention because of its ability to stimulate the initial acute anabolic response. However, a substantial body of both acute and longitudinal research has now accumulated on the topic, affording the ability to scrutinize the effects of BCAA and leucine from a practical standpoint. This article aims to critically review the current literature and draw evidence-based conclusions about the putative benefits of BCAA or leucine supplementation on muscle strength and hypertrophy as well as illuminate gaps in the literature that warrant future study.